Interprofessional empathy: A four-stage model for a new understanding of teamwork. Issue 6 (2nd November 2018) - Adamson, Keith; Loomis, Colleen; Cadell, Susan; Verweel, Lee C.
ABSTRACT: Collaboration in healthcare implies that health providers share responsibility and partner with each other in order to provide comprehensive patient care. A review of the empirical literature on teamwork in healthcare settings suggests that the relationships between service providers remain conflictual and variable in commitment to interprofessional collaboration. Recently, social psychologists have given considerable attention to the possibility that empathy could be used to improve intergroup attitudes and relations. Although empathy may be referred to as a means to humanize healthcare practices, few published studies from the healthcare literature focus on the nature of interprofessional empathy. Understanding frameworks different from your own and empathizing with other members of the team is fundamental to collaborative practice. The aim of this study was to understand the nature of empathy among members of interprofessional teams within a hospital environment. This study followed the lived experience of 24 health professionals with their perspective of empathy on interprofessional teams. A two-step procedure was used consisting of semi-structured interviews and depth interviews. Phenomenological data analysis was used to identify common themes and meanings across interviews. From the findings, a four-stage developmental model of interprofessional empathy emerged: Stage 1 is engaging in conscious interactions; Stage 2 requires using dialogical communication; Stage 3 is obtained when healthcare professionals consolidate understanding through negotiating differences between each other; and Stage 4 shows mastery of nurturing the collective spirit. Knowledge of this stage model will provide clinicians with the information necessary to develop awareness of how day-to-day activities within their interprofessional teams influence the development of interprofessional empathy.